1997
DOI: 10.1099/00222615-46-7-597
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different techniques in the diagnosis of Toxoplasma encephalitis

Abstract: This study evaluated the detection of antibodies, circulating antigens and parasite DNA by polymerase chain reaction (PCR) in the diagnosis of toxoplasma encephalitis. The detection of antibody classes and IgG avidity were not useful diagnostically. The detection of circulating antigens by the ELISA system described was not sufficiently sensitive. The detection of DNA by PCR was the most useful test especially in untreated patients, with a sensitivity of 62% overall, 8lY0 in untreated patients and only 20% in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…The authors suggested that regarding to heterogeneity in the appearance of lesions on T2-weighted images is hard to make a definitive diagnosis based on signal characteristics alone, as it is the case presented here with no diagnosis within one month of admission. It has been proposed that the transition from hyperintensity to isointensity may reflect a response to antibiotic therapy, and that such signal changes could be used to assess the effectiveness of medical therapy (8). Similar findings in our case with loss of hyperintensity on T2-weighted images and transition to isointensity on T1-weighted images after specific therapy parallel to clinical improvement support this opinion.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The authors suggested that regarding to heterogeneity in the appearance of lesions on T2-weighted images is hard to make a definitive diagnosis based on signal characteristics alone, as it is the case presented here with no diagnosis within one month of admission. It has been proposed that the transition from hyperintensity to isointensity may reflect a response to antibiotic therapy, and that such signal changes could be used to assess the effectiveness of medical therapy (8). Similar findings in our case with loss of hyperintensity on T2-weighted images and transition to isointensity on T1-weighted images after specific therapy parallel to clinical improvement support this opinion.…”
Section: Discussionsupporting
confidence: 88%
“…However, serological tests may not be useful for the diagnosis of CNS involvement as in our patient who had high serum IgG titers with no IgM antibodies and a high avidity rate. It has been noticed that the detection of antibodies and IgG avidity were not diagnostic and the detection of serum antigens by enzyme linked immunosorbent assay (ELISA) had a low sensitivity (8). The test with the highest diagnostic yield was the detection of DNA by polymerase chain reaction (PCR) which was also diagnostic in our patient.…”
Section: Discussionmentioning
confidence: 78%
“…Knowledge of the specific treatment and the sample collection during the first week of specific therapy is an important tool for PCR sensitivity (34,40). In agreement, we only collected CSF samples from patients who had received anti-toxoplasmosis treatment up to day 3.…”
Section: Discussionmentioning
confidence: 51%
“…These issues include variations in techniques [17] and standardization in microbiology laboratories. Interpretation of PCR results should also take into consideration whether the patient is receiving specific treatment [15].…”
Section: Diagnosismentioning
confidence: 99%